83‐3L: Late‐News Paper: A Novel High Reactive and High Reliable Monomer for Polymer‐Sustained Alignment Liquid Crystal Displays. Issue 1 (May 2017) - Inoue, Yuichi; Gushiken, Marina; Sudo, Go; Kosaka, Shota; Hayashi, Masanao; Shimizu, Kenta; Takachi, Manabu
Abstract : The Polymer Sustained Alignment (PSA) technology is widely used for Liquid Crystal Display (LCD) TV application etc., because of its high transmittance, high contrast ratio and fast response. In this study, we have developed a novel high reactive and high reliable monomer for PSA. Also we found UV irradiation condition had a huge impact on Image Sticking issue, we propose the optimal UV condition for our new monomer too.